COMPREHENSIVE REVIEW ON IMPLEMENTING A HOSPITAL-BASED RADIOLOGY NURSING ORIENTATION PROGRAM FOR NEW GRADUATE PEDIATRIC NURSES - 1Faisal Hamedsoudalsharari, 2Hasan Musferabdullahalsaloom, 3Hadi Hassan Mana Almakaeel,4Jaber Mana Jaberalmushyif, 5Mohammed Salemhamadalhabes, 6Ali Saleh Mohammed Al Alshahi, 7Ali Abdulrhman Abdu Sofyani, 8Majdi Mohammed Ibrahim Khawaji; 9Nawaf Mabrok Nami Almutairy, 10Rayan Khalid Ali Alzahrani, 11Mahmoud Mohammed Alanazi, 12Abdulrahman Owaidh Atgan Alharbi (Chelonian Research Foundation, 2023)
This review gives an in-depth examination of the utilization of hospital-based electronic well-being administrations in clinical care for new graduate nurses. It is centred on giving them the essential information and aptitudes to illuminate the special issues displayed in pediatric radiology. It incorporates a diagram of the start of the program, a collection of important information, a portrayal of the strategies utilized, an introduction to the program, and counting pictures, tables, and charts. The taking-after talk digs into the suggestions of the discoveries and concludes with conclusions and suggestions planned to advise future generations in this field. Keywords: Radiology nursing, pediatric nursing, orientation program, new graduate nurses, comprehensive review.